ANTI CANCEROUS EFFICACY OF AYURVEDIC MILK EXTRACT OF SEMECARPUS ANACARDIUM NUTS ON HEPATOCELLULAR CARCINOMA IN WISTAR RATS - Joseph, Joice P.; Raval, Sunant K.; Sadariya, Kamlesh A.; Jhala, Mayur; Kumar, Pranay (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of the study was to determine the anticancerous efficacy of Ayurvedic preparation made of Semecarpus anacardium (SA) nuts. Five groups of rats were used for the study. Group I served as water control. Hepatocellular carcinoma (HCC) was induced in groups II, III and IV animals using N-nitrosodiethylamine as inducing agent followed by phenobarbitone as promoter for 13 weeks. Group-II animals were kept untreated as hepatocellular carcinoma control. Group-III animals were treated with Ayurvedic milk extract of Semecarpus anacardium nuts at dose mentioned in Ashtangahridaya, an authentic book of Ayurveda for 49 days and group-IV animals were treated with doxorubicin as reference drug at dose of 1mg/kg twice a week for 7 weeks. Group V animals were kept as drug (SA nut milk extract) control for studying the effect of nut milk extract on normal rats. After 154 days of experiment, all animals were subjected to screening for HCC by estimation of liver enzymes, HCC marker (alpha-2 macroglobulin) and histopathology. Both liver enzymes and HCC marker were increased in hepatocellular carcinoma control along with neoplastic changes in liver and were decreased in Semecarpus anacardium nut milk extract treated group. The Ayurvedic drug showed positive correlation with the action of doxorubicin. This study demonstrated the efficacy of Semecarpus anacardium nut milk extract for the treatment of hepatocellular carcinoma either alone or along with chemotherapy.